Evidence for long-lived mRNA during fruiting body formation in myxococcus xanthus. - Nelson, D R (1983)
Half-lives of Myxococcus xanthus mRNA were determined by inhibiting RNA polymerase with rifampin and then measuring the rate of [35S]methionine incorporation into protein. Vegetative cells resuspended in clone fruiting liquid culture showed an average mRNA half-life of approximately 3.5 min. Developmental cells (24 or 48 hr) exhibited biphasic decay curves with apparent mRNA half-lives of approximately 3.5 min and 20-30 min. The more-stable mRNA species accounted for about 30% of all mRNA present in 24-hr cells and as much as 40% of all mRNA of 48-hr cells. Analysis of the 35S-labeled proteins by NaDodSO4/polyacrylamide gel electrophoresis showed that only 5-10 major polypeptides are synthesized after 30 min of rifampin treatment. One of these is protein S, the spore surface coat protein, because immunoprecipitation of the 35S-labeled proteins with antisera specific for protein S showed continued synthesis of protein S in the presence of rifampin. The half-life for its mRNA was calculated to be 15-30 min. RNA from vegetative and developing cells was pulse labeled with 32PO4 followed by rifampin treatment. Analysis of the labeled RNA on 3% NaDodSO4/polyacrylamide gels showed 5-10 long-lived mRNA bands in developing cells. These results show that there are several abundant mRNA species synthesized developmentally that are exceptionally long lived. The fact that the majority of the mRNA species show the shorter half-life suggests that developing cells retain the normal mechanism for mRNA degradation.